Rates of maternal infections in 15 health care facilities in Almaty region, Kazakhstan. - Sagalbayeva, Ulzhas; Sadykova, Assel; Kurmanova, Gaukhar; Kurmanova, Almagul; Shensa, Ariel; Kabylova, Saule; Raushanova, Aizhan; Beisbekova, Arailym; Tazhibayeva, Karlygash; Seiduanova, Laura; Linkov, Faina (Bangladesh Journal of Medical Science, 2025)
Background Maternal infections are a significant cause of mortality in Central Asia 1. We present detailed information on maternal mortality for the Almaty region in Kazakhstan using data collected in the framework of the WHO GLOSS(World Health Organization, the global maternal sepsis study and awareness campaign). The purpose of this secondary data analysis and study was to characterize and assess the incidence of maternal infections in health facilities in Kazakhstan with the ultimate goal of improving practices for early detection and management, critical to comprehending the early care techniques. Methods Data was obtained in a one-week prospective cohort study in 15 facilities in the Republic of Kazakhstan using hospital records for all pregnant or recently pregnant women hospitalized with suspected or confirmed infections. The ratio of infections and infection-related severe maternal outcomes/1000 live births was calculated, and the distribution of demographic, obstetric, clinical characteristics and outcomes were analyzed using descriptive statistics. Chi-square tests were used to assess associations between demographic and clinical characteristics and infection severity. Results Information was collected on 137 pregnant or recently pregnant women with suspected or confirmed infection. This sample was characterized into three groups by infection severity: Group A, “less severe” (73%), group B, moderately severe (17.5%), and group C, most severe (9.5%). The rate of suspected or confirmed maternal infections in Kazakhstan was 93.7 pregnant and postpartum women per 1,000 live births, which is higher than the global rate (70.4) and comparable to upper-middle income countries (106.4), which also includes Kazakhstan2. Conclusions In this first investigation of maternal sepsis in Kazakhstan, we found that the frequency of maternal infections requiring treatment is higher than in other LMICs. Results show that maternal infections contribute substantially to maternal mortality. Introducing effective evidence-based preventive practices will improve early detection and management of infections in health facilities. BJMS, Vol. 24 No. 03 July’25 Page : 938-945